High-wear-resistance EPDM rubber material and preparation method thereof
By treating lignocellulose with sodium hydroxide and ethyl orthosilicate, combined with nanosilica and graphene oxide, vulcanization is carried out using silane coupling agent and sulfur to form a three-dimensional network structure, the EPDM rubber material is solved in high-level The problems of insufficient cracks and wear resistance in loads and harsh environments have significantly improved their mechanical and wear resistance.
Patent Information
- Application Number
- CN202411413865.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2024-12-20
AI Technical Summary
Existing EPDM rubber materials are prone to cracks, deformation or breaking under high load and harsh environmental conditions, and have insufficient wear resistance, resulting in short product service life and high maintenance and replacement costs.
By treating lignocellulose with sodium hydroxide and ethyl orthosilicate, combined with nanosilica and graphene oxide, vulcanized with silane coupling agent and sulfur to form a three-dimensional network structure to enhance the mechanical and wear resistance of the rubber .
It significantly improves the wear resistance and mechanical properties of rubber materials, extends service life, and reduces maintenance and replacement costs.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of rubber materials, in particular to a high-wear-resistant EPDM rubber material and a preparation method thereof. Background Art
[0002] EPDM rubber is a synthetic rubber that has become a key material in many industrial fields due to its excellent weather resistance, heat resistance and aging resistance. First of all, EPDM rubber has excellent weather resistance and UV resistance, and can maintain stable performance under various climatic conditions. Compared with traditional natural rubber, EPDM is more resistant to sunlight, ozone and chemicals in the environment. This makes EPDM an ideal choice for outdoor applications such as building seals, window seals and roof waterproofing materials. Secondly, EPDM rubber can maintain good performance in high temperature environments, and the heat resistance temperature can usually reach 150°C or higher. This high heat resistance makes EPDM widely used in sealing and gasketing applications in the automotive industry, home appliances, and industrial equipment.
[0003] However, under high load and harsh environmental conditions, EPDM materials need to withstand greater mechanical stress. If the mechanical properties are insufficient, the material is prone to cracks, deformation or fracture, resulting in product failure. Therefore, it is necessary to improve the mechanical properties to ensure that the material maintains stability and reliability in long-term use and extend the service life of the material. In addition, in many applications, EPDM rubber materials are often exposed to wear or friction environments, such as the contact surface of automobile tires, industrial conveyor belts, etc. Therefore, it is necessary to improve wear resistance to effectively reduce material wear and loss, reduce maintenance and replacement costs, and extend the product life cycle.
[0004] In order to overcome the defects of the prior art, the present invention provides a highly wear-resistant EPDM rubber material and a preparation method thereof. Summary of the invention
[0005] The object of the present invention is to provide a highly wear-resistant EPDM rubber material and a preparation method thereof, so as to solve the problems in the prior art.
[0006] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0007] A method for preparing a highly wear-resistant EPDM rubber material comprises the following steps:
[0008] Step 1: placing the lignocellulose in a sodium hydroxide solution, reacting at 80-90°C for 4-6 hours, filtering, washing, drying and crushing after the reaction to obtain pretreated lignocellulose; placing the pretreated lignocellulose in an ethyl orthosilicate solution, adjusting the pH to 8.0-8.5, ultrasonically dispersing for 30-40 minutes, reacting at 60-65°C for 12-14 hours, and drying after the reaction to obtain composite lignocellulose;
[0009] Step 2: Disperse the composite lignocellulose in an ethanol solution, adjust the pH to 9-10, add 3-mercaptopropyltriethoxysilane, stir and react at 70-75°C for 10-15h, centrifuge, wash and vacuum dry after the reaction to obtain modified lignocellulose; disperse the nano-silica filler in an ethanol solution, adjust the pH to 9-10, add 3-mercaptopropyltriethoxysilane, stir and react at 70-75°C for 10-15h, centrifuge, wash and vacuum dry after the reaction to obtain modified SiO2 filler;
[0010] Step 3: Disperse graphene oxide in anhydrous ethanol, ultrasonically disperse for 1.0-1.5 hours, add silane coupling agent KH570, reflux at 110-120° C. for 12-14 hours in a nitrogen environment, and after the reaction, filter, wash, and freeze-dry to obtain a modified graphene filler;
[0011] Step 4: pre-mix EPDM, modified wood cellulose and modified SiO2 filler, and knead them at 100-110°C for 3-5 minutes to obtain pretreated rubber; then mix the pretreated rubber, modified graphene filler, paraffin, zinc oxide, stearic acid, antioxidant 4020, accelerator CZ and sulfur, and knead them at 140-160°C for 5-8 minutes to obtain a finished product.
[0012] More optimally, in step 1, the concentration of the sodium hydroxide solution is 2-3wt%.
[0013] More optimally, in step one, the ethyl orthosilicate solution is composed of a mixture of ethyl orthosilicate and ethanol in a volume ratio of (1.0-1.2):4.
[0014] More optimally, in step 2, the reaction mass ratio of composite wood cellulose and 3-mercaptopropyltriethoxysilane is 1:(4.5-5.0).
[0015] More optimally, in step 2, the reaction mass ratio of the nano-silica filler and 3-mercaptopropyltriethoxysilane is 1:(4.0-4.2).
[0016] More optimally, in step three, the reaction mass ratio of graphene oxide and silane coupling agent KH570 is (1.0-1.2):15.
[0017] More optimally, in step four, the mass ratio of EPDM rubber, modified wood cellulose and modified SiO2 filler is 100:(8-10):(45-55).
[0018] More optimally, in step four, the contents of each component of the finished product are: by mass, 90-110 parts of pretreated rubber, 2-3 parts of modified graphene filler, 0.8-1.2 parts of paraffin, 5-7 parts of zinc oxide, 1.5-2.5 parts of stearic acid, 2-3 parts of antioxidant 4020, 2.0-2.5 parts of accelerator CZ, and 1.5-2.0 parts of sulfur.
[0019] Beneficial effects of the present invention:
[0020] The present invention is characterized in that, in step one, composite lignocellulose is prepared by adding lignocellulose, sodium hydroxide solution and tetraethyl orthosilicate solution. In this step, by using sodium hydroxide solution to pretreat the surface of lignocellulose, impurities on the surface of lignocellulose can be removed and the surface activity of the material can be improved. Furthermore, the pretreated lignocellulose is placed in a tetraethyl orthosilicate solution, and a layer of SiO2 is coated on the surface of the pretreated lignocellulose by a sol-gel method to prepare composite lignocellulose. On the one hand, the SiO2 coating layer generated in situ on the surface of the composite lignocellulose can form hydrogen bonds with the rubber macromolecular chain, effectively enhancing the interface performance between the fiber and the rubber matrix; in addition, the SiO2 coating layer can also reduce the interaction between lignocellulose and prevent agglomeration, thereby improving its dispersibility in rubber. On the other hand, lignocellulose is a relatively cheap natural reinforcing material, so by adding a sufficient amount of lignocellulose, graphene fillers can be replaced to improve the mechanical properties of rubber materials, while reducing the overall cost of rubber materials and promoting the sustainable use of resources.
[0021] The present invention is characterized in that, in step 2, the composite lignocellulose and 3-mercaptopropyltriethoxysilane are mixed to prepare modified lignocellulose. Then, the nano-silica filler and 3-mercaptopropyltriethoxysilane are mixed to prepare modified SiO2 filler. In this step, 3-mercaptopropyltriethoxysilane is used to modify the composite lignocellulose and the nano-silica filler respectively, and the reaction principle is that the ethoxy group of 3-mercaptopropyltriethoxysilane can form a chemical bond with the hydroxyl groups on the surfaces of the two materials, thereby introducing mercapto groups on the surfaces of the two materials, and obtaining modified lignocellulose and modified SiO2 filler respectively.
[0022] The present invention is characterized in that, in step three, graphene oxide and silane coupling agent KH570 are mixed to prepare modified graphene filler. In this step, the graphene oxide surface is silane functionalized by adding silane coupling agent KH570, which can reduce the aggregation phenomenon of graphene oxide in the matrix material, enhance the interaction between graphene oxide and rubber matrix, and promote the filler to be more evenly dispersed in the matrix, thereby improving the overall performance of the rubber material; on the other hand, a functional group C=C can be introduced on the surface of the graphene filler, and the rubber matrix also contains a large amount of C=C, so based on the principle of like dissolves like, the modified graphene filler can have good contact with the rubber matrix while strengthening the rubber matrix; at the same time, in the subsequent vulcanization process, sulfur can effectively connect the rubber molecular chain and the unsaturated double bonds in the modified graphene filler by forming sulfur bridges, thereby forming a three-dimensional network structure and improving the comprehensive performance of the rubber matrix.
[0023] The present invention is characterized in that, in step 4, EPDM, modified lignocellulose and modified SiO2 filler are pre-mixed to obtain pre-treated rubber. In this step, EPDM, modified lignocellulose and modified SiO2 filler are first compounded according to a mass ratio of 100: (8-10): (45-55), and the thiol groups on the surfaces of modified lignocellulose and modified SiO2 filler can react with EPDM to obtain pre-treated rubber; in this step, by pre-mixing the modified lignocellulose and modified SiO2 filler with EPDM, the wear-resistant reinforcing material can be fully dispersed in the rubber matrix, significantly improving the wear resistance and mechanical properties of the rubber matrix. Furthermore, the pre-treated rubber, modified graphene filler, paraffin, zinc oxide, stearic acid, antioxidant 4020, accelerator CZ and sulfur are further mixed to obtain a finished product. The sulfur in this step can effectively connect the rubber molecular chain and the unsaturated double bonds in the modified graphene filler by forming a sulfur bridge. The formation of the sulfur bridge allows cross-linking between the rubber molecular chain and the filler to form a three-dimensional network structure. This cross-linked network can significantly improve the mechanical strength and elasticity of the rubber. In summary, the finished rubber material prepared by the present invention has good wear resistance and mechanical properties, and therefore has broad application prospects in the field of rubber material technology. DETAILED DESCRIPTION
[0024] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0025] Source of raw materials:
[0026] Lignocellulose, provided by Wen'an Xinbao Cellulose Co., Ltd., with a fiber length of 300 μm; nano-silica filler, provided by Jinan Zhongbei Fine Chemical Co., Ltd., model white carbon black ZB-1300; graphene oxide, provided by Lingshou Jianshi Mineral Powder Factory, with a particle size of 2000 mesh; EPDM, provided by Shanghai Oushuo Plastic Co., Ltd., model HYRB; paraffin, provided by Jinan Shanzheng Trading Co., Ltd., model 70#.
[0027] Example 1: Step 1: placing lignocellulose in a sodium hydroxide solution with a concentration of 3wt%, reacting at 90°C for 6h, filtering, washing, drying and crushing after the reaction to obtain pretreated lignocellulose; placing the pretreated lignocellulose in an ethyl orthosilicate solution, adjusting the pH to 8.5, ultrasonically dispersing for 40min, reacting at 65°C for 14h, and drying after the reaction to obtain composite lignocellulose; the ethyl orthosilicate solution is composed of a mixture of ethyl orthosilicate and ethanol in a volume ratio of 0.3:1;
[0028] Step 2: Disperse the composite lignocellulose in an ethanol solution, adjust the pH to 10, then add 3-mercaptopropyltriethoxysilane, stir and react at 75°C for 15 hours, centrifuge, wash and vacuum dry after the reaction to obtain modified lignocellulose; disperse the nano-silica filler in an ethanol solution, adjust the pH to 10, then add 3-mercaptopropyltriethoxysilane, stir and react at 75°C for 15 hours, centrifuge, wash and vacuum dry after the reaction to obtain modified SiO2 filler; the reaction mass ratio of the composite lignocellulose and 3-mercaptopropyltriethoxysilane is 1:5; the reaction mass ratio of the nano-silica filler and 3-mercaptopropyltriethoxysilane is 1:4;
[0029] Step 3: Disperse graphene oxide in anhydrous ethanol, ultrasonically disperse for 1.5 hours, then add silane coupling agent KH570, reflux at 120°C for 14 hours under nitrogen environment, and obtain modified graphene filler by suction filtration, washing, and freeze-drying after the reaction. The reaction mass ratio of graphene oxide to silane coupling agent KH570 is 1:15;
[0030] Step 4: pre-mixing EPDM rubber, modified wood cellulose and modified SiO2 filler, and kneading at 110° C. for 5 minutes to obtain pre-treated rubber; the mass ratio of EPDM rubber, modified wood cellulose and modified SiO2 filler is 20:2:9;
[0031] Then 110 parts of pretreated rubber, 3 parts of modified graphene filler, 0.8 parts of paraffin, 7 parts of zinc oxide, 2.5 parts of stearic acid, 3 parts of antioxidant 4020, 2.5 parts of accelerator CZ, and 2.0 parts of sulfur were mixed and kneaded at 160° C. for 8 minutes to obtain a finished product.
[0032] Example 2: Step 1: placing lignocellulose in a sodium hydroxide solution with a concentration of 3wt%, reacting at 85°C for 5h, filtering, washing, drying and crushing after the reaction to obtain pretreated lignocellulose; placing the pretreated lignocellulose in an ethyl orthosilicate solution, adjusting the pH to 8.3, ultrasonically dispersing for 35min, reacting at 63°C for 13h, and drying after the reaction to obtain composite lignocellulose; the ethyl orthosilicate solution is composed of a mixture of ethyl orthosilicate and ethanol in a volume ratio of 0.3:1;
[0033] Step 2: Disperse the composite lignocellulose in an ethanol solution, adjust the pH to 9.5, then add 3-mercaptopropyltriethoxysilane, stir and react at 73°C for 13 hours, centrifuge, wash and vacuum dry after the reaction to obtain modified lignocellulose; disperse the nano-silica filler in an ethanol solution, adjust the pH to 9.5, then add 3-mercaptopropyltriethoxysilane, stir and react at 73°C for 13 hours, centrifuge, wash and vacuum dry after the reaction to obtain modified SiO2 filler; the reaction mass ratio of the composite lignocellulose and 3-mercaptopropyltriethoxysilane is 1:5; the reaction mass ratio of the nano-silica filler and 3-mercaptopropyltriethoxysilane is 1:4;
[0034] Step 3: Disperse graphene oxide in anhydrous ethanol, ultrasonically disperse for 1.3 hours, then add silane coupling agent KH570, reflux react at 115°C for 13 hours under nitrogen environment, and after the reaction, filter, wash, and freeze-dry to obtain modified graphene filler; the reaction mass ratio of graphene oxide and silane coupling agent KH570 is 1:15;
[0035] Step 4: pre-mixing EPDM rubber, modified wood cellulose and modified SiO2 filler, and kneading at 105° C. for 4 minutes to obtain pre-treated rubber; the mass ratio of EPDM rubber, modified wood cellulose and modified SiO2 filler is 20:2:9;
[0036] Then 110 parts of pretreated rubber, 3 parts of modified graphene filler, 0.8 parts of paraffin, 7 parts of zinc oxide, 2.5 parts of stearic acid, 3 parts of antioxidant 4020, 2.5 parts of accelerator CZ, and 2.0 parts of sulfur were mixed and kneaded at 150° C. for 6 minutes to obtain a finished product.
[0037] Example 3: Step 1: placing lignocellulose in a sodium hydroxide solution with a concentration of 3wt%, reacting at 80°C for 4h, filtering, washing, drying and crushing after the reaction to obtain pretreated lignocellulose; placing the pretreated lignocellulose in an ethyl orthosilicate solution, adjusting the pH to 8.0, ultrasonically dispersing for 30min, reacting at 60°C for 12h, and drying after the reaction to obtain composite lignocellulose; the ethyl orthosilicate solution is composed of a mixture of ethyl orthosilicate and ethanol in a volume ratio of 0.3:1;
[0038] Step 2: Disperse the composite lignocellulose in an ethanol solution, adjust the pH to 9, then add 3-mercaptopropyltriethoxysilane, stir and react at 70°C for 10 hours, centrifuge, wash, and vacuum dry after the reaction to obtain modified lignocellulose; then disperse the nano-silica filler in an ethanol solution, adjust the pH to 9, then add 3-mercaptopropyltriethoxysilane, stir and react at 70°C for 10 hours, centrifuge, wash, and vacuum dry after the reaction to obtain modified SiO2 filler; the reaction mass ratio of the composite lignocellulose and 3-mercaptopropyltriethoxysilane is 1:5; the reaction mass ratio of the nano-silica filler and 3-mercaptopropyltriethoxysilane is 1:4;
[0039] Step 3: Disperse graphene oxide in anhydrous ethanol, ultrasonically disperse for 1.0 h, then add silane coupling agent KH570, reflux at 110° C. for 12 h in a nitrogen environment, and after the reaction, filter, wash, and freeze-dry to obtain a modified graphene filler; the reaction mass ratio of graphene oxide to silane coupling agent KH570 is 1:15;
[0040] Step 4: pre-mix EPDM rubber, modified wood cellulose and modified SiO2 filler, and knead at 100° C. for 3 minutes to obtain pre-treated rubber; the mass ratio of EPDM rubber, modified wood cellulose and modified SiO2 filler is 20:2:9;
[0041] Then 110 parts of pretreated rubber, 3 parts of modified graphene filler, 0.8 parts of paraffin, 7 parts of zinc oxide, 2.5 parts of stearic acid, 3 parts of antioxidant 4020, 2.5 parts of accelerator CZ, and 2.0 parts of sulfur were mixed and kneaded at 140° C. for 5 minutes to obtain a finished product.
[0042] Comparative Example 1: The 3-mercaptopropyltriethoxysilane modification treatment in step 2 is removed, and the rest is the same as Example 1, and the specific steps are as follows: Step 1: Place the lignocellulose in a sodium hydroxide solution with a concentration of 3wt%, react at 90°C for 6h, and after the reaction is completed, filter, wash, dry, and crush to obtain pretreated lignocellulose; place the pretreated lignocellulose in an ethyl orthosilicate solution, and adjust the pH to 8.5, then ultrasonically disperse for 40min, and then react at 65°C for 14h. After the reaction is completed, dry to obtain composite lignocellulose; the ethyl orthosilicate solution is composed of a mixture of ethyl orthosilicate and ethanol in a volume ratio of 0.3:1;
[0043] Step 2: Disperse graphene oxide in anhydrous ethanol, ultrasonically disperse for 1.5 hours, then add silane coupling agent KH570, reflux at 120°C for 14 hours under nitrogen environment, and after the reaction, filter, wash, and freeze-dry to obtain modified graphene filler; the reaction mass ratio of graphene oxide to silane coupling agent KH570 is 1:15;
[0044] Step 3: pre-mixing EPDM rubber, composite wood cellulose and nano-silica filler, and kneading at 110° C. for 5 minutes to obtain pre-treated rubber; the mass ratio of EPDM rubber, composite wood cellulose and nano-silica filler is 20:2:9;
[0045] Then 110 parts of pretreated rubber, 3 parts of modified graphene filler, 0.8 parts of paraffin, 7 parts of zinc oxide, 2.5 parts of stearic acid, 3 parts of antioxidant 4020, 2.5 parts of accelerator CZ, and 2.0 parts of sulfur were mixed and kneaded at 160° C. for 8 minutes to obtain a finished product.
[0046] Comparative Example 2: The two steps in step 4 are combined into one step, and the rest are the same as Example 1, and the specific steps are as follows: Step 1: Place the lignocellulose in a sodium hydroxide solution with a concentration of 3wt%, react at 90°C for 6h, and after the reaction is completed, filter, wash, dry, and crush to obtain pretreated lignocellulose; place the pretreated lignocellulose in an ethyl orthosilicate solution, and adjust the pH to 8.5, then ultrasonically disperse for 40min, and then react at 65°C for 14h. After the reaction is completed, dry to obtain composite lignocellulose; the ethyl orthosilicate solution is composed of a mixture of ethyl orthosilicate and ethanol in a volume ratio of 0.3:1;
[0047] Step 2: Disperse the composite lignocellulose in an ethanol solution, adjust the pH to 10, then add 3-mercaptopropyltriethoxysilane, stir and react at 75°C for 15 hours, centrifuge, wash and vacuum dry after the reaction to obtain modified lignocellulose; disperse the nano-silica filler in an ethanol solution, adjust the pH to 10, then add 3-mercaptopropyltriethoxysilane, stir and react at 75°C for 15 hours, centrifuge, wash and vacuum dry after the reaction to obtain modified SiO2 filler; the reaction mass ratio of the composite lignocellulose and 3-mercaptopropyltriethoxysilane is 1:5; the reaction mass ratio of the nano-silica filler and 3-mercaptopropyltriethoxysilane is 1:4;
[0048] Step 3: Disperse graphene oxide in anhydrous ethanol, ultrasonically disperse for 1.5 hours, then add silane coupling agent KH570, reflux at 120°C for 14 hours under nitrogen environment, and obtain modified graphene filler by suction filtration, washing, and freeze-drying after the reaction. The reaction mass ratio of graphene oxide to silane coupling agent KH570 is 1:15;
[0049] Step 4: Mix 70 parts of EPDM, 7 parts of modified wood cellulose, 33 parts of modified SiO2 filler, 3 parts of modified graphene filler, 0.8 parts of paraffin, 7 parts of zinc oxide, 2.5 parts of stearic acid, 3 parts of antioxidant 4020, 2.5 parts of accelerator CZ, and 2.0 parts of sulfur, and knead at 160°C for 8 minutes to obtain the finished product.
[0050] Comparative Example 3: The mass ratio of EPDM, modified wood cellulose and modified SiO2 filler was changed from 100:(8-10):(45-55) to 100:5:60, and the rest was the same as Example 1. The specific steps were as follows:
[0051] Step 1: placing the lignocellulose in a sodium hydroxide solution with a concentration of 3wt%, reacting at 90°C for 6h, filtering, washing, drying and crushing after the reaction to obtain pretreated lignocellulose; placing the pretreated lignocellulose in an ethyl orthosilicate solution, adjusting the pH to 8.5, ultrasonically dispersing for 40min, reacting at 65°C for 14h, and drying after the reaction to obtain composite lignocellulose; the ethyl orthosilicate solution is composed of a mixture of ethyl orthosilicate and ethanol in a volume ratio of 0.3:1;
[0052] Step 2: Disperse the composite lignocellulose in an ethanol solution, adjust the pH to 10, then add 3-mercaptopropyltriethoxysilane, stir and react at 75°C for 15 hours, centrifuge, wash and vacuum dry after the reaction to obtain modified lignocellulose; disperse the nano-silica filler in an ethanol solution, adjust the pH to 10, then add 3-mercaptopropyltriethoxysilane, stir and react at 75°C for 15 hours, centrifuge, wash and vacuum dry after the reaction to obtain modified SiO2 filler; the reaction mass ratio of the composite lignocellulose and 3-mercaptopropyltriethoxysilane is 1:5; the reaction mass ratio of the nano-silica filler and 3-mercaptopropyltriethoxysilane is 1:4;
[0053] Step 3: Disperse graphene oxide in anhydrous ethanol, ultrasonically disperse for 1.5 hours, then add silane coupling agent KH570, reflux at 120°C for 14 hours under nitrogen environment, and obtain modified graphene filler by suction filtration, washing, and freeze-drying after the reaction. The reaction mass ratio of graphene oxide to silane coupling agent KH570 is 1:15;
[0054] Step 4: pre-mixing EPDM rubber, modified wood cellulose and modified SiO2 filler, and kneading at 110° C. for 5 minutes to obtain pre-treated rubber; the mass ratio of EPDM rubber, modified wood cellulose and modified SiO2 filler is 100:5:60;
[0055] Then 110 parts of pretreated rubber, 3 parts of modified graphene filler, 0.8 parts of paraffin, 7 parts of zinc oxide, 2.5 parts of stearic acid, 3 parts of antioxidant 4020, 2.5 parts of accelerator CZ, and 2.0 parts of sulfur were mixed and kneaded at 160° C. for 8 minutes to obtain a finished product.
[0056] Detection test:
[0057] Mechanical property test: The finished product prepared by the present invention is made into a dumbbell-shaped specimen, referring to GB / T528-2009 standard, the specimen thickness is 7 mm, and the specimen tensile rate is 30 mm / min.
[0058] Wear resistance test: The finished product prepared by the present invention is used as a sample, and the wear resistance of the sample is tested by an Akron abrasion machine according to GB / T 1689-1998 standard, with the pre-wear set to 600 revolutions and the fixed wear set to 3500 revolutions, and the volume wear amount of the sample is calculated according to the formula. The results are as follows:
[0059] <![CDATA[Tensile strength / MPa > <![CDATA[Volume wear amount / cm 3 > Example 1 26.7 0.091 Example 2 26.7 0.092 Example 3 26.6 0.093 Comparative Example 1 25.3 0.109 Comparative Example 2 25.8 0.097 Comparative Example 3 23.6 0.102
[0060] Conclusion: The dosage of Examples 1 to 3 remains unchanged, and only some reaction parameters are modified. From the experimental data, it can be seen that there is no obvious fluctuation in the performance of the samples.
[0061] Comparative Example 1: The 3-mercaptopropyltriethoxysilane modification treatment in step 2 was removed, and the rest was the same as in Example 1. From the experimental data, it can be seen that compared with Example 1, the tensile strength was reduced to 25.3 MPa, and the volume wear amount was increased to 0.109 cm 3 The reasons are analyzed as follows: after the 3-mercaptopropyltriethoxysilane modification treatment is removed, the dispersibility of the nano-silica filler decreases, and agglomeration occurs between the fillers, reducing the mechanical properties and wear resistance of the rubber matrix; in addition, since the modified cellulose and modified SiO2 fillers modified with 3-mercaptopropyltriethoxysilane in the original step four can undergo a mercapto-ene click reaction with the ethylene propylene diene rubber EPDM, thereby achieving a sufficient mixing reaction between the rubber matrix and the filler fibers, the mechanical properties and wear resistance of the sample decrease after the 3-mercaptopropyltriethoxysilane modification treatment is removed.
[0062] Comparative Example 2: The two steps in step 4 are combined into one step, and the rest is the same as Example 1. From the experimental data, it can be seen that compared with Example 1, the tensile strength is reduced to 25.8MPa, and the volume wear amount is increased to 0.097cm 3 The reason for this is that in the original step four, EPDM, modified wood cellulose and modified SiO2 filler were pre-blended and kneaded in order to achieve a sufficient mixing reaction between the rubber matrix and the filler fiber through a chemical reaction. Therefore, after the two steps were combined into one step, compared with Example 1, the dispersibility of the sample decreased, and thus the mechanical properties and wear resistance of the sample decreased.
[0063] Comparative Example 3: The mass ratio of EPDM, modified wood cellulose and modified SiO2 filler was changed from 100:(8-10):(45-55) to 100:5:60, and the rest was the same as Example 1. From the experimental data, it can be seen that compared with Example 1, the tensile strength was reduced to 23.6MPa, and the volume wear amount was increased to 0.102cm 3 The reason is analyzed as follows: in step 4, EPDM, modified wood cellulose and modified SiO2 filler are compounded in a mass ratio of 100:(8-10):(45-55). Under this ratio setting, the three components are fully mixed and reacted, which can effectively improve the comprehensive performance of the rubber matrix, reduce the inconsistency of the finished product performance caused by the uneven dispersion of fibers, fillers and rubber matrix, and improve the overall quality stability of the finished product. Therefore, when the ratio is changed, the mechanical properties and wear resistance of the sample decrease.
[0064] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process method article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process method article or device.
[0065] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a highly wear-resistant EPDM rubber material, characterized in that: The following steps are involved: Step 1: placing the lignocellulose in a sodium hydroxide solution, reacting at 80-90°C for 4-6 hours, filtering, washing, drying and crushing after the reaction to obtain pretreated lignocellulose; placing the pretreated lignocellulose in an ethyl orthosilicate solution, adjusting the pH to 8.0-8.5, ultrasonically dispersing for 30-40 minutes, reacting at 60-65°C for 12-14 hours, and drying after the reaction to obtain composite lignocellulose; Step 2: Disperse the composite lignocellulose in an ethanol solution, adjust the pH to 9-10, add 3-mercaptopropyltriethoxysilane, stir and react at 70-75°C for 10-15h, centrifuge, wash and vacuum dry after the reaction to obtain modified lignocellulose; disperse the nano-silica filler in an ethanol solution, adjust the pH to 9-10, add 3-mercaptopropyltriethoxysilane, stir and react at 70-75°C for 10-15h, centrifuge, wash and vacuum dry after the reaction to obtain modified SiO2 filler; Step 3: Disperse graphene oxide in anhydrous ethanol, ultrasonically disperse for 1.0-1.5 hours, add silane coupling agent KH570, reflux at 110-120° C. for 12-14 hours in a nitrogen environment, and after the reaction, filter, wash, and freeze-dry to obtain a modified graphene filler; Step 4: pre-mix EPDM, modified wood cellulose and modified SiO2 filler, and knead them at 100-110°C for 3-5 minutes to obtain pretreated rubber; then mix the pretreated rubber, modified graphene filler, paraffin, zinc oxide, stearic acid, antioxidant 4020, accelerator CZ and sulfur, and knead them at 140-160°C for 5-8 minutes to obtain a finished product.
2. The method for preparing a highly wear-resistant EPDM rubber material according to claim 1, characterized in that: In step 1, the concentration of the sodium hydroxide solution is 2-3wt%.
3. The method for preparing a highly wear-resistant EPDM rubber material according to claim 1, characterized in that: In step 1, the ethyl orthosilicate solution is composed of a mixture of ethyl orthosilicate and ethanol in a volume ratio of (1.0-1.2):
4.
4. The method for preparing a highly wear-resistant EPDM rubber material according to claim 1, characterized in that: In step 2, the reaction mass ratio of the composite wood cellulose and 3-mercaptopropyltriethoxysilane is 1: (4.5-5.0)。 5. The method for preparing a highly wear-resistant EPDM rubber material according to claim 1, characterized in that: In step 2, the reaction mass ratio of the nano-silica filler and 3-mercaptopropyltriethoxysilane is 1:(4.0-4.2).
6. The method for preparing a highly wear-resistant EPDM rubber material according to claim 1, characterized in that: In step three, the reaction mass ratio of graphene oxide and silane coupling agent KH570 is (1.0-1.2):
15.
7. The method for preparing a highly wear-resistant EPDM rubber material according to claim 1, characterized in that: In step 4, the mass ratio of EPDM rubber, modified wood cellulose and modified SiO2 filler is 100:(8-10):(45-55).
8. The method for preparing a highly wear-resistant EPDM rubber material according to claim 1, characterized in that: In step 4, the contents of the components of the finished product are: by mass, 90-110 parts of pretreated rubber, 2-3 parts of modified graphene filler, 0.8-1.2 parts of paraffin, 5-7 parts of zinc oxide, 1.5-2.5 parts of stearic acid, 2-3 parts of antioxidant 4020, 2.0-2.5 parts of accelerator CZ, and 1.5-2.0 parts of sulfur.
9. A highly wear-resistant EPDM rubber material, characterized in that: Prepared according to the preparation method according to any one of claims 1 to 8.
Citation Information
Cited By
Wear-resistant sealing rubber strip and preparation method thereof
CN120923928A
Regenerated polyester stock solution colored sea-island composite fiber material and preparation method thereof
CN121065853A
A regenerated polyester dope colored sea-island composite fiber material and a preparation method thereof
CN121065853B
Ethylene-propylene-diene monomer rubber sealing strip and preparation method thereof
CN122011604A
